Processable and recyclable polyurethane/HNTs@Fe3O4 solid–solid phase change materials with excellent thermal conductivity for thermal energy storage. Issue 12 (6th October 2021) - Lin, Changhong; Ying, Puyou; Huang, Min; Zhang, Ping; Yang, Tao; Liu, Gang; Wu, Jianbo; Levchenko, Vladimir
Abstract: The permanently chemically cross‐linking solid–solid phase change materials (SSPCMs) were designed to solve the problem of leakage and poor shape stability during the whole process of phase transformation. However, these materials lead to environment pollution and resources waste because of the non‐recyclability. Therefore, a SSPCMs was fabricated using dynamic thermal reversible Diels–Alder bonds. The prepared SSPCMs exhibited excellent shape, heat storage stability, and reliability and reprocessed ability, resulting from dynamic Diels–Alder bonds. Moreover, the Halloysite nanotubes decorated with Fe3 O4 nanoparticles (HNTs@Fe3 O4 ) were used to enhance the thermal conductivity of SSPCMs. When the filler content was 0.5 wt%, the best integrated properties (phase change properties and thermal conductivity) of the SSPCMs were obtained, it had the highest melting and freezing phase change enthalpies about 116.8 and 127.2 J/g, and thermal conductivity value, 0.223 W/m K, which was 101% higher than pure SSPCMs. Hence, the prepared SSPCMs can be considered as promising save‐energy, friendly‐environment thermal management materials. Abstract : In this work, processable and recyclable solid‐solid phase change materials (SSPCMs) were synthesized by thermal dynamic reversible Diels–Alder crosslinking and high thermal conductivity filler (HNTs@Fe3O4). These SSPCMs can be used to fabricate multifunctional save‐energy, friendly‐environment phase change materials to replace the pure polymers.